The impact of diabetes in head and neck cancer. Issue 2 (April 2020) - Vilaseca, Isabel; Fuster, Gemma; Avilés-Jurado, Francesc-Xavier
Abstract : Purpose of review: A strong association between diabetes mellitus and carcinogenesis has been reported in different organs. The purpose of this review is to summarize the new evidences in relation to diabetes mellitus and its association with the development, prognosis, and therapeutic strategies of head and neck squamous cell carcinomas (HNSCC). Recent findings: Recent publications suggest that glycemic metabolism is altered in HNSCC. Elevated blood glucose levels, before or around the time of diagnosis, have been reported to reduce survival rates in HNSCC. Also, the homeostasis model assessment-insulin resistance has been independently associated with disease-free survival, suggesting that improving the glycemic control may improve the prognosis in this group of patients. Epidemiological studies revealed that cancer patients with diabetes mellitus have less cancer-related mortality after antiglycemic treatment, opening the option to include antiglycolytic agents, such as metformin, in the therapeutic plan. This finding is in accordance with in-vitro studies that demonstrated a decrease in tumor-cell proliferation with antidiabetic medications. Summary: Recent findings highlight the importance of glucose metabolism in the pathogenesis and progression of cancer cells. The knowledge of these altered pathways gives us an opportunity to design target treatments aimed to modulate glucose catabolism.